Factors Predicting the Physical Activity Behavior of Female Adolescents: A Test of the Health Promotion Model - Hashem Mohamadian; Mohammad Ghannaee Arani (Korean Society for Preventive Medicine, 2014)
ObjectivesPhysical activity behavior begins to decline during adolescence and continues to decrease throughout young adulthood. This study aims to explain factors that influence physical activity behavior in a sample of female adolescents using a health promotion model framework.MethodsThis cross-sectional survey was used to explore physical activity behavior among a sample of female adolescents. Participants completed measures of physical activity, perceived self-efficacy, self-esteem, social support, perceived barriers, and perceived affect. Interactions among the variables were examined using path analysis within a covariance modeling framework.ResultsThe final model accounted for an R2 value of 0.52 for physical activity and offered a good model-data fit. The results indicated that physical activity was predicted by self-esteem (β=0.46, p<0.001), perceived self-efficacy (β=0.40, p<0.001), social support (β=0.24, p<0.001), perceived barriers (β=-0.19, p<0.001), and perceived affect (β=0.17, p<0.001).ConclusionsThe findings of this study showed that the health promotion model was useful to predict physical activity behavior among the Iranian female adolescents. Information related to the predictors of physical activity behavior will help researchers plan more tailored culturally relevant health promotion interventions for this population.